1975
DOI: 10.1128/jb.121.3.942-949.1975
|View full text |Cite
|
Sign up to set email alerts
|

6-Phosphogluconate dehydratase deficiency in pleiotropic carbohydrate-negative mutant strains of Pseudomonas aeruginosa

Abstract: Mutants of Pseudomonas aeruginosa, strain PAO, have been isolated that are unable to grow on mannitol, glucose, gluconate, or 2-ketogluconate, but that exhibit wild-type growth on pyruvate, lactate, citrate, succinate, or acetate. Although some of these mutants were also unable to grow on glycerol, the mutations formed a single linkage group by quantitative transductional analysis with phage F116 on glucose minimal agar medium. Cell extracts of all mutant strains were either lacking or severely deficient in 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

1977
1977
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
0
25
1
Order By: Relevance
“…It was early suggested that glycerol catabolism relies on a functional and active ED pathway in P. aeruginosa (Blevins et al, 1975;Heath and Gaudy, 1978) and in P. putida (Aparicio et al, 1971;Vicente and Cánovas, 1973). Heath and Gaudy (1978) proposed that glycerol metabolism depends on the activation of GAPDH and, therefore, on an active metabolism of the hexosephosphate derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…It was early suggested that glycerol catabolism relies on a functional and active ED pathway in P. aeruginosa (Blevins et al, 1975;Heath and Gaudy, 1978) and in P. putida (Aparicio et al, 1971;Vicente and Cánovas, 1973). Heath and Gaudy (1978) proposed that glycerol metabolism depends on the activation of GAPDH and, therefore, on an active metabolism of the hexosephosphate derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Since the assay depends upon the conversion of NADPf into NADPH, absolute values of enzyme activity should be regarded with caution. In a study of carbohydrate catabolism in mutant strains of P. aeruginosa (Blevins et al, 1975), increased 6-phosphogluconate dehydrogenase activity was detected only in those strains containing elevated levels of Entner-Doudoroff enzymes. The generation of glyceraldehyde 3-phosphate by this pathway may provide substrate for endogenous glyceraldehyde-3-phosphate dehydrogenase, thus creating errors in the assay.…”
Section: R E S U L T Smentioning
confidence: 99%
“…Longer incubation led to a faint growth on fructose plates. Mutants lacking the dehydrase and the aldolase of the Entner-Doudoroff pathway were impaired iti growth on most substrates, the dehydrase mutant being glycerol positive (2).…”
Section: Synthesismentioning
confidence: 99%
“…Glycerol metabolism also culminates in the production of glyceraldehyde 3-phosphate as depicted in Fig. 5 through glycerol kinase, aglycerophosphate dehydrogenase, and triose phosphate isomerase (2). It would be interesting to examine the behavior of mutants lacking fructose diphosphatase and fructose diphosphate aldolase.…”
Section: Downloaded Frommentioning
confidence: 99%